2017
DOI: 10.1021/acs.jnatprod.7b00500
|View full text |Cite
|
Sign up to set email alerts
|

A Bis-benzopyrroloisoquinoline Alkaloid Incorporating a Cyclobutane Core and a Chlorophenanthroindolizidine Alkaloid with Cytotoxic Activity from Ficus fistulosa var. tengerensis

Abstract: Tengerensine (1), isolated as a racemate and constituted from a pair of bis-benzopyrroloisoquinoline enantiomers, and tengechlorenine (2), purified as a scalemic mixture and constituted from a pair of chlorinated phenanthroindolizidine enantiomers, were isolated from the leaves of Ficus fistulosa var. tengerensis, along with three other known alkaloids. The structures of 1 and 2 were determined by spectroscopic data interpretation and X-ray diffraction analysis. The enantiomers of 1 were separated by chiral-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The plates were terminated by MTT cell proliferation assay at 72 hours after treatment. 23,24 Calcusyn 2.1 software (Biosoft, Cambridge, UK) was used to generate combination index (CI) based on Chou-Talalay method, 19,25 in which CI < 1, = 1 and >1 indicates synergism, additive and antagonism effect, respectively (Table S3). The dose-response surface curves with levels of HSA synergy were plotted by Combenefit software (Cancer Research UK Cambridge Institute).…”
Section: Drug Combination Analysismentioning
confidence: 99%
“…The plates were terminated by MTT cell proliferation assay at 72 hours after treatment. 23,24 Calcusyn 2.1 software (Biosoft, Cambridge, UK) was used to generate combination index (CI) based on Chou-Talalay method, 19,25 in which CI < 1, = 1 and >1 indicates synergism, additive and antagonism effect, respectively (Table S3). The dose-response surface curves with levels of HSA synergy were plotted by Combenefit software (Cancer Research UK Cambridge Institute).…”
Section: Drug Combination Analysismentioning
confidence: 99%
“…Table 3 where the entries are in bold characters. (A) chlorinated phenanthroindolizidine (Al-Khdhairawi et al, 2017); (B) 3,4-seco-lupane-type triterpenoid ; (C) asteriscunolide C (Boumaraf et al, 2017); (D) (+)-strebloside ; (E) Glycybridin D ; (F) (-)-neocaryachine ; (G) plectranthroyleanone A (Nzogong et al, 2018); (H) uncarilin A (Geng et al, 2017); (I) 27-hydroxyalphitolic acid derivative (Novakovic et al, 2017) The following chemical names were given when the structures were fairly simple. For other more complex skelettons (AM, AP, AQ, AR, AU and AV), common names were given that correspond to the global structure of the core molecule.…”
Section: Different Strategies To Benefit From This Diversitymentioning
confidence: 99%
“…In this review, we list in Table 2 we found that most compounds exhibited moderate cytotoxicity with IC 50 values ranging from 10 to 50 μM. 22,25,27,33,38,40,45,46,53,68,80,[83][84][85][86][87][88]90,93,98,101,105,159 Three Amaryllidaceae alkaloids, lycorine (321), haemanthamine (326), and haemanthidine 327 Table 2. Higher antiproliferative effects also were reported.…”
Section: Various Isoquinoline Alkaloidsmentioning
confidence: 99%